Is the small island effect observed in the courtyards of a historical city centre? - Kozlov Mikhail V; Zverev Vitali (TAYLOR & FRANCIS LTD, 2022)
Growing evidence suggests that biodiversity on small islands and fragments could be independent of island area, a pattern called the Small Island Effect (SIE). We searched for SIE among the floras of 19 courtyards completely enclosed by buildings in central St Petersburg, Russia, in 1993, 2003 and 2008. Despite the extremely small size of the studied habitats (125-3500 m(2); open ground area 0.1-700 m(2)), the number of native and naturalized vascular plant species generally increased with an increase in habitat area. Plant species richness was better explained by the open ground area than by the total courtyard area, and species-area relationships did not differ between ornamental and non-ornamental plants. The statistical support for SIE was obtained in 3 of 14 analyses. Both semi-log and log-log data demonstrated SIE in trees, but not in shrubs or herbs. We also found SIE in the 2008 data (all life forms combined), but only with a semi-log model. The threshold area for the detected SIE was 3-7 m(2). We conclude that SIE in urban green spaces may be an exception rather than the general rule. Its occurrence may be transient and may depend on the current balance of stochastic colonisation and extinction processes. Thus, even a minor increase in the area of open ground patches embedded in an urban matrix will increase the diversity of plants persisting in these patches. This finding justifies the importance of small local actions for maximizing the conservation of urban biodiversity and the retention of the ecosystem services it provides.